IMPELEMENTATION OF BUSINESS STRATEGY IN THE STATE-OWNED CORPORATION - Widiarto, Ardian; Arraniri, Iqbal; Filatrovi, Eldes Willy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Since January 2015 the government has begun to abolish some product subsidies, especially for the marketing area of Java Bali and Madura. This opens up opportunities for new players to enter the oil and gas sector given the increasingly promising profits. the emergence of this new competitor adds to fierce competition between outlets, and to maintain cost efficiency a flexibility strategy and innovation strategy are implemented, especially related to the distribution of products from the company to all outlets where transportation equipment is adjusted so that it can transport various types of products to several outlets at a time . This condition is accompanied by a policy that a conveyance may send to various outlets at a time. Initially, business performance improved rapidly but with the increasing number of outlets there were several product distribution accidents, subsidized deposits, customers switching to other outlets including those owned by foreign companies, and backlog transaction constraints. The problem is that the partner's trust has declined including customers to the company as a result of very strict supervision in the midst of environmental changes as a result of changes in government policies and regulations lately. The sample became the object of research is customer stations in Central Java and Yogyakarta as many as 200 customer in the Gas Station Central Java and Yogyakarta. Methods of data analysis used in this study is a quantitative analysis method where quantitative data analysis method is a method of analysis in the form of figures and calculations using statistical methods. In simplify the analysis process, will be used SEM, AMOS. Keywords : Product Cohesiveness, Quality Business Strategy, Business Performance, Competitive Advantage